Postoperative Hearing Outcomes and Usefulness of Endoscopy-Assisted Tympanoplasty in Pars Tensa Cholesteatoma - Kurioka, Takaomi; Mizutari, Kunio (International Archives of Otorhinolaryngology, 2025)
Introduction In recent years, transcanal endoscopic ear surgery (TEES) has gained widespread recognition as an excellent surgical field for blind spots such as the sinus tympani (ST) when compared to microscopic ear surgery (MES).Objective To investigate the postoperative hearing results for pars tensa cholesteatoma and the indications for utilizing endoscopy.Methods The medical records of 16 patients (10 men and 6 women) with pars tensa cholesteatoma, who received initial surgical treatment between 2018 and 2022, were reviewed. We performed MES, TEES, or endoscopy-assisted MES (dual approach) depending on the pathological involvement in the mastoid cavity and ST.Results The mean age of the patients was 45 years, and the surgical techniques utilized were MES in 2 cases, TEES in 7 cases, and dual approach in 7 cases. The preoperative pathological classification was stage I in 3 patients and stage II in 13 patients. The overall surgical success rates of postoperative hearing outcomes were 69% and 50% (1/2 patients) in the TEES group, 71% (5/7 patients) in the MES group, and 71% (5/7 patients) in the dual approach group. The successful cases (n = 11) were significantly younger and demonstrated better mastoid pneumatization than unsuccessful cases (n = 5).Conclusion Endoscopy-assisted MES is appropriate for treating pars tensa cholesteatoma when pathological involvement is present at the deep bottom of the ST. Early surgical intervention and good eustachian tube function are crucial for improving hearing prognosis. Transcanal endoscopic ear surgery can be particularly useful in identifying and removing residual cholesteatoma within the ST.
Keywords: middle ear; cholesteatoma; tympanoplasty; hearing loss; endoscopy